2018
DOI: 10.1016/j.pbb.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from behavior and developmental effects of chronic oral methylphenidate following an abstinence period

Abstract: Chronic oral methylphenidate (MP) exposure in rats is associated with numerous developmental and behavioral consequences. The present study investigated the persistence of the effects of chronic oral MP exposure after abstinence from MP use. Male and female rats were exposed to daily orally self-administered water, low dose MP (LD), or high dose (HD) MP for 13 weeks, followed by a 4-week abstinence period. Fluid, food consumption and bodyweights were monitored and animals were tested for locomotor activity, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 53 publications
6
25
0
Order By: Relevance
“…Previous studies reported a dose‐related locomotor‐increasing characteristic of chronic MP exposure (Griggs et al, ; Kuczenski & Segal, ; Penner, McFadyen, Carrey, & Brown, ; Yang, Swann, & Dafny, ). Indeed, similar to our previous reports following uninterrupted 13‐week daily MP exposure (Martin et al, ; Robison, Michaelos, et al, ) and 13‐week daily MP exposure with weekend abstinence periods (Carias et al, ), chronic MP consumption increased locomotor activity in this study. This effect was evident from the increased floor‐plane distance, floor plane move time, and center distance in the open field in the HD MP‐treated group compared to both LD and water groups during the treatment phase.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Previous studies reported a dose‐related locomotor‐increasing characteristic of chronic MP exposure (Griggs et al, ; Kuczenski & Segal, ; Penner, McFadyen, Carrey, & Brown, ; Yang, Swann, & Dafny, ). Indeed, similar to our previous reports following uninterrupted 13‐week daily MP exposure (Martin et al, ; Robison, Michaelos, et al, ) and 13‐week daily MP exposure with weekend abstinence periods (Carias et al, ), chronic MP consumption increased locomotor activity in this study. This effect was evident from the increased floor‐plane distance, floor plane move time, and center distance in the open field in the HD MP‐treated group compared to both LD and water groups during the treatment phase.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our previous findings following chronic uninterrupted exposure (Martin et al, ; Robison, Michaelos, et al, ) and chronic exposure with weekend abstinence periods (Carias et al, ), we observed attenuated anxiety‐like behaviors in the HD compared to both LD and water groups during the treatment phase. This finding corroborates existing evidence that MP administration exerts an anxiolytic effect on pre‐pubertal mice (Carrey, ), adult mice prenatally exposed to MP (McFadyen‐Leussis, Lewis, Bond, Carrey, & Brown, ) and on adult rats (Britton & Bethancourt, ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We hypothesized that during the treatment phase, chronic MP exposure, regardless of weekend abstinence, would produce the same effects as we previously reported [11]. Furthermore, we expected the effects of chronic MP treatment to be generally reversed following prolonged abstinence, as our recent data indicated [23]. The present study examined the behavioral consequences of chronic weekday-only oral MP treatment in rats and revealed that HD MP exposure resulted in increased open field and circadian locomotor activity; increased latency to immobility and decreased time spent immobile in the forced swim test; increased center activity in the open field and percent of time spent in an open arm of the elevated-plus-maze; and increased social affiliation and memory in the Crawley’s three chamber sociability test.…”
Section: Introductionmentioning
confidence: 73%